Direct observation of narrow mid-infrared plasmon linewidths of single metal oxide nanocrystals - Robert W. Johns (Nature Portfolio, 2016)
Establishing the cause of inhomogeneous broadening would help to produce narrow ensemble localized surface plasmon resonance peaks, favourable for sensing applications. Here, Johns et al. use near field optics for enhancing signal contrast, enabling the measurement of mid-infrared spectra of single nanocrystals.